Normalization of China-Indonesia's diplomatic relations and the role of the mianzi concept - Muas, R. Tuty Nur Mutia Enoch (Wacana, Journal of the Humanities of Indonesia, 2012)
This thesis examines the normalization of China-Indonesia's diplomatic relations in order to understand China's main motivation. The "micro-macro linkage" approach is used to uphold the empirical evidence that is enhanced by the mianzi concept. In Chinese culture, mianzi consists of honourable values and meanings. The result of this research shows that the changes in China's foreign policy priority have been caused by the demise of the socialist power in the late 1980s and the Tiananmen incident in 1989. Threat to China's sovereignty and unity has been the basis of the priority to keep the country's honour and existence. The term baoquan mianzi is used in this matter. It means using the whole potential of the Chinese people to defend the country's honour. The People's Republic of China's international image and glory need to be restored. The normalization of diplomatic relations has proven to be part of baoquan mianzi effort and has given China a big opportunity to participate in regional and global forums.